Studi Pelacakan Alumni Keguruan STKIP Andi Matappa - Sitti Busyrah Muchsin; Hasbahuddin Hasbahuddin (JURKAM: Jurnal Konseling Andi Matappa, 2018)
This research was conducted with the aim of: 1) Digging information from alumni about the development of competencies needed by the labor market for curriculum improvement materials; 2) Conduct workplace tracking, work area, waiting time to get a job, first salary, current job, and other information from alumni of Andi Matappa. The tracer study design uses a sensory survey that is the target population of the study is 2015 graduated cohort with a total of 213 graduates, of whom 136 are from Guidance and Counseling and 95 from Mathematics Education. The data collection method used is the online method using QTAFI software (Question Table and Figure). The instrument used is a fully adapted Indotrace standard questionnaire that includes questions listed in the core questionnaire of Tracer Study Online Kemristekdikti. The results showed that alumni need a maximum of 5 months to get the first job after graduation and the three highest ways to get it through relationships, internet and advertising work. Amount 71% of alumni STKIP Andi Matappa work in government agencies. The majority of graduates have worked according to the field of science pursued during the study period, but need strengthening in some respects especially in the ability of foreign languages and computers so that graduates can work in accordance with the development of Science and Technology.